A proof of Chen-Males̆ević’s conjecture - Wang, Fen; Xiao, Hai-Yan (Revista de la Real Academia de Ciencias Exactas, Físicas y Naturales. Serie A, Matemáticas, 2024)
In this paper, we obtain a new inequality between the inverse hyperbolic tangent and inverse sine functions, which is a conjecture of Chen-Males̆ević [(Chen in Rev Real Acad Cienc. Exactas Fis. Nat. Ser. A-Mat 114:105, 2020) conjecture 2.1]spsCM.